Labour resistance and worker attitudes towards trade union reform in China - Kan Wang (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Purpose - Drawing its arguments and conclusion from a ten-year survey on workers’ experiences of labor disputes, along with anticipation of trade union reform, the purpose of this paper is to discuss the interaction between labor resistance and its potential for institutional change in the field of labor relations in China.    Findings: An increase in collectivized disputes in China has given rise to an escalation of labor action, characterized by wildcat strikes. Joint action has strengthened the bonds among work colleagues, and it has become more important for workers to pay attention to their rights and interests. In terms of organization, two viewpoints towards union reform were revealed: the pragmatist and the idealist perspectives. Workers with greater experience of resistance were more modest in terms of demands for union reform, while workers with some experience called for their union’s independence from the party-state.